Ecological Discourses in KPK School Textbooks: An Ecolinguistic Analysis of English and Science Texts at Grades 8, 9, and 10 Applying Stibbe’s Framework - Muhammad Suhaib; Muhammad Ihteram; Laila Afridi (University of Chitral Journal of Linguistics and Literature, 2024)
This paper focuses on the language and graphical representation of the environmental problems and nature in English and Science textbooks of Grades 8, 9, and 10 in Khyber Pakhtunkhwa (KPK), Pakistan. By applying the ecolinguistic framework by Stibbe (2015), the study analyses textbook discourses as beneficial, ambivalent, or destructive, using investigative tools such as representation of nature, lexical pattern analysis, metaphorical framing, and visual discourse analysis. Data was collected exclusively from assigned textbook chapters and pages. The findings indicate that ambivalent and destructive discourses which portray nature as a resource, threat, or passive object are predominant while Beneficial discourses that promote ecological care and agency are underrepresented. The paper emphasizes the need to reform the curriculum to integrate ethically grounded and ecocentric narratives and description that foster environmental responsibility among students.